Field instrumentation for monitoring of water, heat, and gas transfers through unsaturated soils - Indrawan, I. Gde Budi (2013)
In this paper, measurement details of pore-water pressures, volumetric water contents, temperatures, and relative oxygen concentrations in unsaturated soil layers under asphalt pavement, aeration slab, and turf cover, as well as weather conditions are described. Measurement results show that positive pore-water pressures developed frequently in the soil layers under the asphalt pavement. Volumetric water contents of the soil layers near the ground surface fluctuated highly as compared to those of the soil layers below. Magnitude and fluctuation of temperatures in the soil layers under the asphalt pavement were the highest while those beneath the turf cover were the lowest. Oxygen concentrations in the soil layers under turf cover increased faster than those in the soil layers under the asphalt pavement and aeration slab. By conducting comprehensive and continuous measurements, relationship between pore-water pressures and volumetric water contents can be obtained and mechanisms of water, heat and gas transfers through unsaturated soil under different surface conditions can be better understood.